The Asian Green Mussel Perna viridis in the Canal do Itajurú, Brazil: Establishment in a Hypersalinity-Influenced Coastal Channel - Bruno Pereira Masi; Márcio A. Siqueira; Alexandre R. da Silva; Júlio C. Monteiro; Alexandre D. Kassuga; Luciana Altvater; Luciana V. R. Messano; Ricardo Coutinho (Thalassas: An International Journal of Marine Sciences, 2026)
The Asian green mussel, Perna viridis , is a globally successful invasive bivalve first recorded in the South Atlantic in 2018. Here, we report and characterize the establishment of P. viridis in the Canal do Itajurú, a coastal channel connecting the hypersaline Araruama Lagoon to the Atlantic Ocean in Rio de Janeiro, Brazil. We assessed its spatial distribution, substrate association, and morphometric variation to evaluate local establishment and potential ecological and management implications. Perna viridis was recorded along nearly the entire channel and was strongly associated with artificial substrates, including vessels, ropes, buoys, bridge structures, and concrete rubble. Morphometric variation indicated larger individuals on more stable artificial structures, suggesting that these habitats may favor population development. Although the Canal do Itajurú is part of a hypersaline lagoon system and is subject to elevated and variable salinity, salinity was not measured during the biological survey; therefore, this occurrence should be interpreted as evidence of establishment in a hypersalinity-influenced coastal channel. The concentration of mussels on artificial substrates in economically important areas underscores the role of recreational vessels and maritime infrastructure as vectors and settlement habitats. These findings highlight the need for continuous monitoring, public awareness, and antifouling strategies to reduce further dispersal and establishment in vulnerable coastal ecosystems.